Radiotherapy Response of Cervical Cancer Patients at a Tertiary Referral Hospital in Indonesia - Winarto, Hariyono; Rahakbauw, Erwin; Supriana, Nana (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To investigate the response of radiotherapy and related clinicopathologic characterictics on cervical cancer patients. Methods: This was a retrospective study. Subjects were patients diagnosed with cervical cancer stage IIA-IIIB who had undergone radiation therapy based on standard protocol in our hospital, during the period of January 2014 to December 2015. The clinical factors ofthose patients, such as age, Body Mass Index, blood pressure, hemoglobin level, blood leucocyte count, serum albumin, largest tumor diameter, the International Federation of Gynecology and Obstetrics (FIGO) staging, as well as pathologic characteristic, i.e histopathology and grading were recorded. During radiation protocol until 3months post radiation, we also noted any side effects of gastrointestinal tract, genitourinary tract, and hematologic. Evaluation of radiotherapy response was based on Response Evaluation Criteria in Solid Tumors (RECIST).  Results: A total of 123 subjects were enrolled in this study. 84 cases or 68.29% was complete response, 30 cases or 24.39% was partial response, 6 cases or 4.88% was stabile response, and 3 cases or 2.44% was progressive. Based on gastrointestinal side effect, there was no side effect or grade 0 on 99 cases (80.49%), grade 1 on 20 cases (16.26%), grade 2 on 4 cases (3.25%), grade 3 on 0 case (0%). Based on side effect of genitourinary, there was no side effect or grade 0 on 105 cases (85.37%), grade 1 on 17 cases (13.82%), grade 2 on 1 case (0.81%), grade 3 on 0 case (0%). Based on hematologic side effects, there was no side effecton 108 cases (87.80%), grade 1 on 15 cases (12.20%), grade 2 on 0 case (0%), grade 3 on 0 case (0%). Largest tumor diameter was statistically significant, with p=0.036 (RR 2.64 (1.07-6.56)). Conclusion: The majority of definitive-curative radiotherapy response on cervical cancer stage IIA-IIIB was complete (68.29%). Acute side effects involving the gastrointestinal, genitourinary, and hematologic system were commonly can be tolerable during and 3 months post radiation therapy. Clinicopathologic characteristics significantly associated with the complete response of radiotherapy was the largest tumor diameter. Keywords: largest tumor diameter, radiation response, radiationside effect